2017
DOI: 10.18632/oncotarget.22541
|View full text |Cite
|
Sign up to set email alerts
|

GPER is involved in the regulation of the estrogen-metabolizing CYP1B1 enzyme in breast cancer

Abstract: The cytochrome P450 1B1 (CYP1B1) is a heme-thiolate monooxygenase involved in both estrogen biosynthesis and metabolism. For instance, CYP1B1 catalyzes the hydroxylation of E2 leading to the production of 4-hydroxyestradiol that may act as a potent carcinogenic agent. In addition, CYP1B1 is overexpressed in different tumors including breast cancer. In this scenario, it is worth mentioning that CYP1B1 expression is triggered by estrogens through the estrogen receptor (ER)α in breast cancer cells. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
5
17
0
Order By: Relevance
“…These results suggest that these three metabolic genes may have oncogenic roles in basal-like TNBC development. In line with our finding, CYP1B1, a heme-thiolate monooxygenase mainly expressed in endocrine-regulated tissues like breast, has been shown to be overexpressed in breast cancer, including basal-like TNBCs [30]. CYP1B1 has an oncogenic role in cancer due to its role in the metabolism of 17β-estradiol (E2) and E2-like molecules, which causes DNA adducts and generates free radicals leading to DNA damage and tumorigenesis in different tissues like breast [30].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…These results suggest that these three metabolic genes may have oncogenic roles in basal-like TNBC development. In line with our finding, CYP1B1, a heme-thiolate monooxygenase mainly expressed in endocrine-regulated tissues like breast, has been shown to be overexpressed in breast cancer, including basal-like TNBCs [30]. CYP1B1 has an oncogenic role in cancer due to its role in the metabolism of 17β-estradiol (E2) and E2-like molecules, which causes DNA adducts and generates free radicals leading to DNA damage and tumorigenesis in different tissues like breast [30].…”
Section: Resultssupporting
confidence: 85%
“…In line with our finding, CYP1B1, a heme-thiolate monooxygenase mainly expressed in endocrine-regulated tissues like breast, has been shown to be overexpressed in breast cancer, including basal-like TNBCs [30]. CYP1B1 has an oncogenic role in cancer due to its role in the metabolism of 17β-estradiol (E2) and E2-like molecules, which causes DNA adducts and generates free radicals leading to DNA damage and tumorigenesis in different tissues like breast [30]. Consistently, TPH1, an enzyme involved in serotonin (5-hydroxytryptamine or 5-HT) biosynthesis via catalyzing tryptophan metabolism, has been shown to be overexpressed in basal-like TNBC cell lines like MDA-MB-231 [31].…”
Section: Resultssupporting
confidence: 85%
“…To test this hypothesis, we performed gene set enrichment analyses (GSEA) using transcriptomic data compiled by the Broad Institute on 60 human breast cancer cell lines in the Cancer Cell Line Encyclopedia (CCLE) [ 72 ]. Although it is recognized that several factors contribute to CYP1B1 expression [ 73 , 74 , 75 ], CYP1B1 levels were chosen as an approximation of AHR activity for three reasons: (1) We and others previously demonstrated that baseline CYP1B1 mRNA levels are maintained to a large extent by “constitutively active” AHR in human breast cancer cell lines [ 46 , 76 ]. (2) There is a strong correlation between AHR and CYP1B1 mRNA levels in the 60 breast cancer cell lines in the CCLE ( r = 0.64; FDR < 4 × 10 −7 ) and in 995 primary human breast cancers in The Cancer Genome Atlas (TCGA) ( r = 0.27; FDR < 2.3 × 10 −16 ) databases [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the stimulatory effects elicited by GPER on the growth of diverse cancer cells [ 3 , 4 , 5 , 6 ], high doses of the GPER agonist G-1 (≥1 μM) have been shown to exert an inhibitory action on the proliferation of certain cancer cell lines [ 52 , 53 , 54 , 55 , 56 ]. Therefore, the different biological responses mediated by GPER in distinct tumor cell contexts may depend on the receptor expression repertoire, the signaling pathways activated and other factors that remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens play a crucial role in diverse pathophysiological conditions, including cancer [ 1 ]. The action of estrogens are mainly mediated by the classic estrogen receptors (ERs) [ 2 ], however several data have also indicated that the G protein estrogen receptor (GPER) may trigger a network of transduction pathways toward the progression of several types of tumors [ 3 , 4 , 5 , 6 , 7 , 8 ]. Among numerous biological targets, estrogens may modulate the expression of diverse microRNAs (miRNAs) [ 6 ], which are small non-coding RNA molecules of 22–25 nucleotides [ 9 ].…”
Section: Introductionmentioning
confidence: 99%